Novel side chain functionalized polystyrene/O-PBI blends with high alkaline stability for anion exchange membrane water electrolysis (AEMWE) - Hager, Linus; Hegelheimer, Manuel; Stonawski, Julian; Freiberg, Anna T.S.; Jaramillo-Hernández, Camilo; Abellán, Gonzalo; Hutzler, Andreas; Böhm, Thomas; Thiele, Simon; Kerres, Jochen (Journal of Materials Chemistry A, 2023)
We report the synthesis of a polystyrene-based anion exchange polymer bearing the cationic charge at a C6-spacer. The polymer is prepared by a functionalized monomer strategy. First, a copper halide catalyzed C-C coupling reaction between a styryl Grignard and 1,6-dibromohexane is applied, followed by quaternization with N-methylpiperidine and free radical polymerization. The novel polymer is blended with the polybenzimidazole O-PBI to yield mechanically stable blend membranes representing a new class of anion exchange membranes. In this regard, the ratio of the novel anion exchange polymer to O-PBI is varied to study the influence on water uptake and ionic conductivity. Blend membranes with IECs between 1.58 meq. OH− g−1 and 2.20 meq. OH− g−1 are prepared. The latter shows excellent performance in AEMWE, reaching 2.0 A cm−2 below 1.8 V in 1 M KOH at 70 °C, with a minor degradation rate from the start. The blend membranes show no conductivity loss after immersion in 1 M KOH at 85 °C for six weeks indicating high alkaline stability.
CRIS-Team Scopus Importer:2023-11-10